Data Camp Instructional Materials - (:unkn) unknown (My University, 2016)
These materials where used for the 3-week instruction camp on research data management held at UWM Libraries in 2016. The camp was run by the Data Services Librarian and intended for other librarians to become more comfortable with data management concepts. The topics covered include: data management best practices, data management plans, and data repositories. Each 1-hour session consisted of 2 hands-on exercises. The first 3 pages of this document provide the general outline for each session, with the exercise handouts making up the rest of the document.
Keywords: data camp; data management; research data management; data services; research data; data repositories; data management plans; data information literacy